Information technology usage, motivation, and intention: a case of Chinese urban senior outbound travelers in the Yangtze River Delta region. Issue 1 (2nd January 2017) - Wang, Wanfei; Wu, Wei; Luo, Jieqing; Lu, Jiaying
ABSTRACT: Chinese outbound travel is thriving, with seniors taking an increasing market share. However, although outbound travel in general has been researched quite well, little is known specifically about the outbound travel behavior of Chinese seniors, or the effects of information technology (IT) on their vacation patterns. This study is an initial and exploratory attempt to understand the relation between IT usage and tourism behavior (travel motivation, travel intention, and sociodemographics) of Chinese senior outbound travelers. The results reveal four segments of IT usage, each with significantly different traveler profiles in terms of sociodemographics, travel motivation, and travel intention.